Analiz final'nych mužskich zaplyvov meždunarodnych sorevnovanij v plavanii 2012-2019 godov - Galyautdinov, M. I.; Lobanov, A. S.; Galyautdinova, L. R.; Sitdikov, A. M.; Miftakhov, R. F. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
This article shows the results analysis of 50 m freestyle final races in Olympic Games 2012 and 2016 years and 14th - 18th FINA World Championships. Based on opened video we made chronometry and strokes counting in 15-50 m line segment. Full time dispersion, and also the time and strokes quantity of the second part of the distance have been researched with the standard deviation. Difference importance of full time and time and strokes quantity for 15-50 m line segment have all been researched through the dispersion analysis and with StatPlus6 program. For those data the posterior results comparison has been made.